Объяснение:
https://tex.z-dn.net/?f=%20%5Csqrt%7B11-4%20%5Csqrt%7B7%7D%7D%2B%20%5Csqrt%7B16-6%20%5Csqrt%7B7%7D%7D%3D%20%5Csqrt%7B7-2%2A2%20%5Csqrt%7B7%7D%2B4%7D%2B%5Csqrt%7B9-2%2A3%2A%5Csqrt%7B7%7D%2B7%7D%3D%20%5C%5C%20%3D%5Csqrt%7B%28%5Csqrt%7B7%7D%29%5E2-2%2A2%20%5Csqrt%7B7%7D%2B2%5E2%7D%2B%5Csqrt%7B3%5E2-2%2A3%2A%5Csqrt%7B7%7D%2B%28%5Csqrt%7B7%7D%29%5E2%7D%3D%20%5C%5C%20%3D%5Csqrt%7B%28%5Csqrt%7B7%7D-2%29%5E2%7D%2B%5Csqrt%7B%283-%20%5Csqrt%7B7%7D%29%5E2%7D%3D%7C%5Csqrt%7B7%7D-2%7C%2B%7C3-%20%5Csqrt%7B7%7D%7C%3D%20%5C%5C%20%3D%5Csqrt%7B7%7D-2%2B3-%20%5Csqrt%7B7%7D%3D1
Это ссылка!
1.
а) (а³ + 2) (а – 3) = a⁴ - 3a³ + 2a - 6
б) (m – 4) ( m + 5) = m² + 5m - 4m - 20 = m²+ m - 20
в) (3х – 1) (2х + 5) = 6x² + 15x - 2x - 5 = 6x² + 13x - 5
г) – 5х (–х – 2) (2х³ – 3 + 4 х) = (5x² + 10x)(2x³-3+4x) = 10x⁵ - 15x² + 20x³ +20x³ - 30x + 40x² = 10x⁵ + 40x³ + 25x² - 30x
2.
а) (х + 2) (х -5) – 3х (1 – 2х) = x² - 5x + 2x - 10 - 3x + 6x² = 7x² - 6x - 10
б) (а + 6) (а – 3) + (а – 4) (а + 5) = a² - 3a + 6a - 18 + (a² +5a - 4a - 20) = a² - 3a + 6a - 18 + a² + 5a - 4a - 20 = 2a² + 4a - 38 | :2 = a² +2a - 19
3.
а) 14х² – (2х – 3) (7х + 4) = 14
14x² - (14x² + 8x -21x - 12) = 14
14x²-14x²+13x=14-12
13x = 2
x = 2/13
б) (2х + 6) (7 – 4х) = (2 – х) (8х + 1) + 15
14x - 8x² + 42 - 24x = (16x + 2 -8x² - x) + 15
-8x² - 10x -15x + 8x² = 15 + 2 - 42
-25x = -25
x = 1
4.
Пусть x - длина прямоугольника, тогда 2x - ширина
⇒
2x² + 7x - 4x - 14 = 2x² + 19
3x = 19 + 14
3x = 33
x = 11 - длина прямоугольника
11 * 2 = 22 - ширина прямоугольника
Найдем производную
Функция убывает на отрезке
Следовательно при
ответ